Methods of conflict management at the aviation industry enterprises - P. A. Alekseeva (Вестник университета)
The article deals with the management of hidden conflicts at the enterprises of the aviation industry. At present, a topical issue for the management of companies is the resource effectiveness of personnel, obtained as a result of the development or implementation of a management decision. The author emphasizes the importance of the conflict management process as a key tool for personnel management, on which the success of the company and sometimes the very existence of the enterprise, largely depends. The purpose of this work is to describe the conflict management methodology at the enterprises of the aviation industry by developing a model for identifying conflicts at an early stage. The main aspects of identifying conflict situations on the basis of modern theory and practice of conflict management are revealed. In this regard, the necessity for the top management of enterprises to make competent, economically sound management decisions is substantiated. A model for identifying hidden conflicts between employees is proposed.